Bone mineral density status in urolithiasis patients with vitamin D inadequacy followed at a tertiary stone centre - Elkoushy, Mohamed Aly; Jundi, Mazen; Lee, Terence T.N.; Andonian, Sero (Canadian Urological Association Journal, 2014)
Introduction: We assessed abnormalities in bone mineral density (BMD) and the risk of hip and major osteoporotic fractures in urolithiasis patients with vitamin D inadequacy (VDI) followed at a tertiary stone centre. Methods: Stone-free patients with VDI were invited to undergo dual-energy x-ray absorptiometry (DXA) scans to assess for BMD abnormalities at the femoral neck and lumbar spine. The World Health Organization’s validated Fracture Risk Assessment Tool (FRAX) was used to calculate the risk of hip and major osteoporotic fractures within 10 years. Patients with primary hyperparathyroidism or hypercalcemia were excluded. Results: In total, 50 consecutive patients were included between June 2011 and August 2012, including 26 (52%) males. The median age was 51 years and the median 25-hydroxyl vitamin D (25[OH]D) was 18.8 ng/mL. Thirty patients (60%) had abnormal T-scores on DXA studies. This decreased to 22 (44%) when age-matched Z-scores were used; 36% had osteopenia and 8% had osteoporosis. Femoral neck and lumbar spines were affected in 24% and 32% of patients, respectively. Recurrent stone-formers had significantly lower BMD when compared with first-time stone-formers. Median serum 25(OH)D was comparable between patients with normal and abnormal DXA scans (18.6 vs. 18.8 ng/mL; p = 0.91). Five patients (10%) were at high risk (≥3%) of hip fractures within 10 years. Conclusion: A high prevalence of abnormal DXA scans was found in urolithiasis patients with VDI, including 5 patients (10%) at high risk of hip fractures. Future studies need to assess the economic impact of obtaining DXA scans on urolithiasis patients with VDI, especially in recurrent stone-formers.